Peran Pembelajaran Vokasional dalam Meningkatkan Kemampuan Komunikasi Verbal Siswa Autis di SLB Negeri Cileunyi - Reliyanti, Euis (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2023)
The increasing number of autistic people urged special schools in Indonesia to run appropriate programs that support the need of people with ASD. One of SMLB's main programs in building the skills of autistic students whose verbal communication skill is limited, is vocational learning program. This study aims to determine types and the role of vocational learning in improving the verbal communication ability of students with ASD. The method used in this research was qualitative method. Data were collected through the techniques of interview with teachers, direct observation of the implementation of vocational learning, as well as document study of the vocational learning procedures. The collected data was then analysed using descriptive analysis technique by Miles and Huberman to draw conclusions. Results showed that the vocational programs provided by the SLB are plant cultivation/animal husbandry, cookery, fashion, cosmetology, simple automotive, and simple Computer Information Technology. In each lesson students are involved in preparing materials/tools, performing activities, and tidying up the tools. During the implementation of vocational learning their verbal communication is trained in real context. Verbally students are introduced to vocabularies about tools and materials, and procedures to do activities using phrases and sentences. Their interaction and communication skills are trained through discussion and collaboration activities in completing activities. With such learning activities it can be concluded that the vocational learning has played a role in improving the verbal communication ability to interact and communicate of the ASD students.